2019
DOI: 10.1002/mus.26687
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of small‐fiber neuropathy in neurofibromatosis type 1

Abstract: Introduction Large‐fiber neuropathy is rare in neurofibromatosis type 1, but small‐fiber neuropathy has not been studied. Methods Patients with neurofibromatosis type 1 underwent nerve conduction studies for large‐fiber assessment. Small‐fiber tests included quantitative thermal thresholds, laser Doppler flare imaging, intraepidermal nerve fiber density, and corneal nerve fiber length. Results Of the 52 patients enrolled, 31 (60%) were female and the mean age was 33.0 ± 12.3 years. Four (8%) patients had abnor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Beading frequency was not considered [ 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 97 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Beading frequency was not considered [ 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 97 ].…”
Section: Resultsmentioning
confidence: 99%
“…Zangh et al reported that in transthyretin familial amyloid polyneuropathy (TTR-FAP) patients all CCM parameters were significantly reduced with disease progression. IWL (Inferior whorl length) ( p = 0.006), CNFL ( p = 0.005), CNBD ( p = 0.008), and CNFD ( p = 0.014) were significantly lower in early-phase patients [ 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…Corneal nerve loss occurs in patients with Charcot Marie Tooth disease type 1A [ 53 ] and in severe peripheral neuropathy associated with a rare nerve growth factor-β mutation [ 54 ]. We have also demonstrated corneal nerve loss in patients with Friedreich’s ataxia [ 55 ] and neurofibromatosis type 1 [ 56 ].…”
Section: Ccm In Other Peripheral Neuropathiesmentioning
confidence: 99%
“…The severity of corneal nerve loss has been related to the number of GAA repeats and clinical disability assessed using the Scale for the Assessment and Rating of Ataxia and Friedreich's Ataxia Rating Scale ( 50 ). In a cohort of 51 patients with neurofibromatosis type 1, 8% had abnormal nerve conduction studies, 13% had abnormal thermal thresholds, 22% had abnormal intraepidermal nerve fiber density, however, 52% had reduced corneal nerve fiber length ( 51 ).…”
Section: Ccm In Peripheral Neuropathiesmentioning
confidence: 99%